Response of Surgical Center Following a Train Accident on JR Fukuchiyama Line : A Instructive Subject for the Future - FUJIMOTO, Yoko (Nihon Rinshō Masui Gakkai shi, 2013)
In disaster situations, the university hospital must be ready to function as a disaster response base, rendering emergency treatments including surgeries on multiple trauma patients in addition to everyday activities. We reviewed the 2005 JR Fukuchiyama line derailment accident from the view-point of the operating room nursing supervisor and analyzed the shortcomings of the response. The 2008 surgical medical practice guidelines of the Japanese Association of Operative Medicine included the train accident as a case study. One of the problems highlighted was that information regarding the numbers and severity of injured patients in need of emergency surgical procedures was constantly changing. Therefore it is important that we remain in constant contact with emergency medical care centers where staff perform triage and initial treatment as well as coordinate with all surgical departments.